Project Profiles - Integrated Child development Services Projects - Planning Commission (Planning Commission Government of India, 1978)
The Integrated Child Development Services (ICDS) Projects Report presents a comprehensive evaluation of ICDS interventions across rural, tribal, and urban areas of India, focusing on maternal and child health and nutrition. Field studies conducted during 1976–78 highlight widespread nutritional deficiencies, including protein and micronutrient inadequacies among children and pregnant or lactating women, often exacerbated by cultural food taboos. Health assessments reveal prevalent conditions such as anemia, malaria, respiratory infections, and gastrointestinal diseases, compounded by poor sanitation and limited access to healthcare infrastructure. Urban slums and tribal regions exhibit unique challenges, including overcrowding, low literacy, inadequate water supply, and insufficient trained health personnel, which limit program effectiveness. The report emphasizes gaps in program coverage, with supplementary nutrition initiatives reaching only a fraction of eligible beneficiaries. Recommendations include strengthening community participation through awareness campaigns and local committees, expanding health infrastructure and staffing, enhancing nutritional education, improving access to safe drinking water, and monitoring program implementation to address disparities. Case studies, such as the Kidderpore ICDS project, illustrate both the potential of ICDS initiatives and the challenges in sustaining community engagement and service delivery. Overall, the report underscores the need for a multifaceted and culturally sensitive approach to improve health and nutrition outcomes for vulnerable children and mothers, advocating for targeted interventions, effective resource allocation, and strengthened local collaboration to achieve sustainable impact.
Programme Evaluation Organisation Planning Commission Government of India New Delhi-110001 1978
Keywords: Integrated Child Development Services; Nutrition; Health; Maternal Health; Child Health; Malnutrition; Tribal Areas; Urban Slums; Community Participation; Health Infrastructure; Dietary Patterns; Supplementary Nutrition